Estimations of restrictions on use “standard” solutions of Vlasov equations for drift waves - Kasilova, E.V.; Khvesyuk, V.I. (Вопросы атомной науки и техники, 2007)
Some estimations of correctness of use “standard” solution of Vlasov equation for finite sistems are curried out. Виконано оцінки коректності використання результатів інтегрування рівняння Власова для систем кінцевих розмірів. Выполнены оценки корректности использования результатов интегрирования уравнения Власова для систем конечных размеров.